A case of glomerulonephritis showing remarkable segmental extracapillary proliferation; Is this a new category disease or not? - Seiji Hashimoto; Risshi Kudo; Mamiko Shimamoto; Rie Yamamoto; Tomochika Maoka; Keisuke Kawashima; Yuichiro Fukazawa; Takao Koike; Takashi Shigematsu (Society of Diabetic Nephropathy Prevention, 2018)
Background: Significant capillary proliferation is common in post-streptococcal acute glomerulonephritis (PSAGN) after streptococci and is a prognostic disease. Focal segmental glomerulosclerosis is a disease characterized by segmental sclerosis although it may have a poor prognosis Case Presentation: A 50-year-old man with nephrotic syndrome underwent renal biopsy, which showed marked endocapillary proliferation due to enlarged vascular endothelial cells and infiltration of lymphocytes. However, there was no mesangial cell proliferation, mesangial matrix increase, or crescent formation. Electron microscopy showed fusion of podocytes without any electron-dense deposits. Immunostaining for CD68 and CD3 was positive, and the presence of macrophages and T-cells was suggested. Steroid therapy, including pulse therapy, was performed, and then cyclosporine was added to steroid therapy. Although urinary protein decreased, his renal function did not respond well to steroid therapy, and the patient initiated dialysis 2 years later. Conclusions: We report this case considering that it was nephritis of unknown origin showing segmental endocapillary proliferation that had not been recognized previously.